Crystal plasticity FE study of the effect of thermo‐mechanical loading on fatigue crack nucleation in titanium alloys. Issue 6 (19th February 2016) - Ozturk, D.; Shahba, A.; Ghosh, S.
Abstract: In this paper, crystal plasticity simulations are conducted with a stabilized finite deformation finite element model to study the effects of microstructure as well as thermal and mechanical loading conditions on fatigue crack nucleation of Ti alloys. The crystal plasticity model includes a non‐local crack nucleation model. Results of simulations are used to understand the effects of dwell loading periods and microtexture on fatigue nucleation life in polycrystalline microstructures in comparison with experiments. From the thermo‐mechanical studies of these alloys, it is found that anisotropic thermal expansion under thermal loading can induce stresses normal to the basal plane, which can help opening up microcracks. Moreover, in agreement with experimental results, the simulations show diminished load shedding at elevated temperature because of weakening of plastic anisotropy.